Організаційно-управлінська реструктуризація металургійних підприємств при переході до проектного управління забезпеченням їх стратегічного розвитку - Шкрабак, І. В.; Skrabak, I. V. (Університет економіки і підприємництва, 2024)
Стаття присвячена актуальним питанням підвищення ефективності управління стратегічним розвитком структур металургійного бізнесу. Обгрунтовано доцільність організаційно-управлінської реструктуризації металургійних підприємств з урахуванням факторів зовнішнього середовища. Визначені глобальні чинники, що зумовлюють необхідність організаційно-управлінських трансформацій, зокрема, перспективність переходу до моделі проектно-орієнтованої організації, і визначені фактори, які виступають суттєвими обмеженнями для металургійних підприємств. Обґрунтовано доцільність системного підходу до використання у якості інструментів здійснення організаційно-управлінської реструктуризації структурних, культурних змін та змін, орієнтованих на персонал, що дозволить зміцнити позиції проектного менеджменту в процесі реалізації завдань стратегічного розвитку металургійних підприємств.

The article addresses the pressing issues of enhancing the efficiency of managing the strategic development of metallurgical business structures. The rationale for the organizational and managerial restructuring of metallurgical enterprises is substantiated, taking into account external environmental factors as well as the socio-political and economic situation in the metallurgical industry. Global factors necessitating organizational and managerial transformations are identified, including the outcomes of the Fourth Industrial Revolution, the global “green” trend, and the development of advanced management concepts and technologies. The transition of metallurgical enterprises to a project-oriented organizational model is presented as a promising direction. Their positions in this transition process are analyzed, and key factors that significantly constrain such enterprises are identified. These include the advantages of traditional organizational management structures, the shortcomings of a strong matrix structure, and situational difficulties in transitioning to professional project management. The relevance of a systematic approach to organizational and managerial restructuring through organizational changes is substantiated. This approach allows for strengthening the role of project management in achieving strategic development goals of metallurgical enterprises without necessitating a full transformation into a project-oriented organization. The main types of organizational changes identified as tools for restructuring include structural, cultural and personneloriented changes. The goals of applying these tools are defined as follows: aligning the organizational foundations of functional and project management, ensuring cross-functionality of personnel with project management competencies, and enhancing the motivational mechanisms that facilitate the development of project management through the implementation of corporate, business, functional, and operational strategies of enterprises. The article also proposes key measures for implementing organizational changes as tools for restructuring.
Organizational and managerial restructuring of metallurgical enterprises in the transition to project management for ensuring their strategic development
Keywords: організаційно-управлінська реструктуризація; чинники; проектний менеджмент; проектно-орієнтована організація; обмеження; організаційні зміни; organizational and managerial restructuring; factors; project management; project-oriented organisation; limits; organizational changes